Read my mind - Sta. Maria, Melencio author (Manila Lorimar Publishing, Incorporated, 2013)
A collection of commentaries Sta. Maria made on news and current events, as well as some human interest stories. Some of them are articles published on InterAksyon.com, where Sta. Maria serves as one of its resident contributors.
Includes index.
Keywords: Maria, Melencio Sta; Journalists -- Philippines -- Biography